Nitrogen-carbon nanotubes as a basis for a new type of semiconductor materials for electronics devices - Irina V. Zaporotskova; Sergey V. Boroznin; Natalia P. Boroznina; Evgeniy S. Dryuchkov; Kseniya Yu. Verevkina; Yulia V Butenko; Pavel A. Zaporotskov; Lev V. Kozhitov; Alena V. Popkova; Aleksandr D. Grigoriev (Modern Electronic Materials)
The use of semiconductor nanomaterials is currently considered to be one of the most promising device optimization methods since those materials allow controlling the electronic properties and possess high mechanical and thermal strength, providing for long device service life without the necessity of replacement or seeking new solutions. The parameters of the electronic and energy structure of new semiconductor nanomaterials based on carbon nanotubes containing substitution atoms have been studied. The test carbon nanotubes contained specific substitution atom concentrations (15, 25 and 50%). A relationship has been drawn between the band gap, conductivity and optical properties of the materials. Data on the band gap and conductivity as functions of substituting nitrogen atom concentration and tube diameter have been reported. The experimental band gap data suggest that the nanotubes in question are narrow-gap semiconductors. One can also conclude that a new semiconductor material has been synthesized on the basis of carbon nanotubes with substitution nitrogen atoms since the test tubes exhibit a redistribution of electron density towards the nitrogen atoms and positive charge localization in the vicinity of the carbon atoms. The results are of utmost importance for the design and fabrication of components and units for nanoelectronics and microsystems: our theoretical study has confirmed the possibility to control the refraction index and conductivity of media by implementing a carbon-for-nitrogen substitution reaction to various concentrations. Thus, a new electronics material has been studied, i.e., carbon nanotubes modified by substitution of nitrogen atoms.